Taking flight : from war orphan to star ballerina - DePrince, Michaela (Ember, 2016)
The autobiography of Michaela DePrince, who lived the first few years of her life in war-torn Sierra Leone until being adopted by an American family. Now seventeen, she is one of the premiere ballerinas in the United States.